Anatomy of gene regulation : a three-dimensional structural analysis - Tsonis, Panagiotis A (Cambridge University Press, 2003)
Anatomy of Gene Regulation is the first book to present the parts and processes of gene regulation at the three-dimensional level. Vivid structures of nucleic acids and their companion proteins are revealed in full-color, three dimensional form. Beginning with a general introduction to three-dimensional structures, the book looks at the organization of the genome, the structure of DNA, DNA replication and transcription, splicing, protein synthesis, and ultimate protein death. This concise and unique synthesis and its accompanying web site offer insight into gene regulation, and into the development of methods to interfere with regulation at diseased states.
Keywords: biologie; geny; Genes